The relationship between agility and vertical jump performance in male handball players: a cross-sectional analysis on the role of developmental characteristics - Ergin, R.; Karci, B. (PLOS ONE, 2025)
Aim This research examines the relationship between agility and vertical jump by controlling for developmental characteristics (age, height, and body weight), which are important for sports performance yet underexplored in literature.